The Effectiveness of Psychodrama in the Treatment of Anxiety for Students of Art Education Department - Al- Salami, Amer Salim Obaid (Journal of Tikrit University for Humanities, 2020)
Anxiety is an emotion that results of the learner’s fear of future and what threaten his being and his life continuation and stability, which made him feel dejected, nervous and psychologically unstable. Therefore, it is necessary to control these fears and threats by the use of psychodrama as a means for the learner to comprehend the world in which he lives through awareness and experiment that help them to cope and assimilate in the society to get rid of anxiety. It appeared to the researcher through a survey study that there is anxiety that overcomes them due to fear of future in case of failing to comprehend the new life tasks. That encouraged him to think of using practical and scientific mechanism to get rid of that anxiety by using the psychodrama to treat some of the psychological cases foremost of which is anxiety. The study is structured in four chapters: Chapter One includes the methodological framework, that is, the problem, importance, objective and hypothesis of the study. The present study aim at examining “the effectiveness of psychodrama in the treatment of anxiety for students of art education department”. To verify the above objective the following zero hypothesis was formulated (there is statistically significant difference at the level of 0.05 between the average score of students of experimental group and control group in the Skill Performance Test) as well as the limit and term definition. Chapter Two is consecrated to the theoretical framework which is sibdivded into two inquiries: the first inq. deals of psychodrama (concept, busies, elements), while the second inq. deals with anxiety (symptoms, types and reasons). Chapter Three deals with the methodology and procedures of study in terms of research community, sample and the experimental design adopted by the researcher for the skill test. Chapter four includes result displat and explanation as well as conclusion and recommendations.